2005
DOI: 10.1103/physrevlett.94.087204
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Antiferromagnetic Order of the Fe Monolayer on W(001): Spin-Polarized Scanning Tunneling Microscopy and First-Principles Calculations

Abstract: We prove that the magnetic ground state of a single monolayer Fe on W(001) is c2 2 antiferromagnetic, i.e., a checkerboard arrangement of antiparallel magnetic moments. Real space images of this magnetic structure have been obtained with spin-polarized scanning tunneling microscopy. An out-ofplane easy magnetization axis is concluded from measurements in an external magnetic field. The magnetic ground state and anisotropy axis are explained based on first-principles calculations. DOI: 10.1103/PhysRevLett.94.08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
109
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(121 citation statements)
references
References 24 publications
10
109
2
Order By: Relevance
“…By manufacturing alloys in different stoichiometries from these two substrate elements, a crossing can be found from the AFM to the FM state of the Fe monolayer [4]. It should be noted that in previous studies [1,4] the Fe layer relaxation on the Ta substrate was assumed to be the same as on W substrate with the reasoning that Ta and W are neighbouring elements in the periodic table. In contrary, we found a considerable difference in the out-of-plane relaxation of the Fe ML on these two substrates, see Table 1.…”
Section: Fe On Bcc Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…By manufacturing alloys in different stoichiometries from these two substrate elements, a crossing can be found from the AFM to the FM state of the Fe monolayer [4]. It should be noted that in previous studies [1,4] the Fe layer relaxation on the Ta substrate was assumed to be the same as on W substrate with the reasoning that Ta and W are neighbouring elements in the periodic table. In contrary, we found a considerable difference in the out-of-plane relaxation of the Fe ML on these two substrates, see Table 1.…”
Section: Fe On Bcc Substratesmentioning
confidence: 99%
“…Ta(001) and W(001) surfaces have been the focus of a number of theoretical and experimental studies [1,2,3,4]. In case of an Fe monolayer on W(001) surface the magnetic ground state is antiferromagnetic, while for the Fe ML on Ta(001) substrate the ground state is ferromagnetic.…”
Section: Fe On Bcc Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been shown that (homoatomic) magnetic monolayers on transition metal substrates may have magnetic structures which are completely different from the bulk materials. 37,38 This is particularly true for triangular lattices where the AFM interaction is frustrated by the symmetry of the system and can result in complex magnetic structures. 39 In this paper we investigate the relative stability of various FeO/Pt(111) interface structures, taking into account different magnetic configurations.…”
Section: Introductionmentioning
confidence: 99%
“…5 Very recently, Kubetzka et al have applied the same technique to study a single monolayer of Fe on W(001), resolving a longstanding question regarding the magnetic ground state of this system. 11 Atomic-scale SP-STM has therefore been established as a powerful technique for resolving the ultimate limits of magnetic structure on surfaces.…”
mentioning
confidence: 99%